Frameworks for Practice (Kairaranga, 2010)
This study investigates the types of assessment models used by registered psychologists employed by Ministry of Education: Special Education (MOE:SE) who work in the area of severe and challenging behaviour. The aim of the study was to identify and explore frameworks for practice which are currently used at MOE:SE; the theories which underpin these as well as which aspects of the frameworks were supportive of multi-agency/multi- disciplinary work.A semi-structured interview format was used to encourage participants to discuss the frameworks and theories which they use during practice in the field. The participants were six randomly-chosen registered psychologists who work at MOE:SE.While responses varied, the most commonly reported frameworks for practice were Effective Interventionsfor Behaviour Challenges, Functional Behavioural Assessment and Situational Analysis. The theories which the participants reported as underpinning their practice were also diverse, although behavioural theory was reportedly used by all participants. Collaboration was reported most often as being a supportive aspect of frameworks which were used during inter-disciplinary/ inter-agency work.